1984
DOI: 10.21236/ada141216
|View full text |Cite
|
Sign up to set email alerts
|

Subgradient Methods in Deterministic and Stochastic Optimization.

Abstract: February 27. 1984 Introduction. Research supported by this two-year grant in the period from January, 1982, through December, 1984, has resulted in a total of 11 technical articles and two doctoral theses. These range over several areas of mathematical optimization theory but share the common theme of the development and application of subgradient methods and duality to problems in mathematical programming. Fundamental advances in concept have been made, and in the case of stochastic problems, new techniques o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Related to the needs of applications in variational analysis a wide literature has been devoted to extensions of convexity and/or smoothness for sets, functions and multifunctions. For real valued functions a robust extension of both convexity and smoothness is given by LC k -functions, or lower -C k (k ∈ N) functions, introduced (for k ≥ 2) by T. Rockafellar (1982) in finite dimension, then extended to infinite dimensional Hilbert space by J. P. Penot (1996). The lower -C 1 functions, due to J. E. Springarn (1981), are characterized by a submonotonicity property of subdifferentials.…”
Section: The Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to the needs of applications in variational analysis a wide literature has been devoted to extensions of convexity and/or smoothness for sets, functions and multifunctions. For real valued functions a robust extension of both convexity and smoothness is given by LC k -functions, or lower -C k (k ∈ N) functions, introduced (for k ≥ 2) by T. Rockafellar (1982) in finite dimension, then extended to infinite dimensional Hilbert space by J. P. Penot (1996). The lower -C 1 functions, due to J. E. Springarn (1981), are characterized by a submonotonicity property of subdifferentials.…”
Section: The Preliminariesmentioning
confidence: 99%
“…Then, J. P. Vial (1983) introduced in finite dimension the weakly convex functions and characterized them as difference of two convex functions (dc-functions). But Rockafellar (1982) and Penot (1996) showed that for all k ≥ 2 the lower -C k functions are lower -C 2 and coincide actually with weakly convex and locally Lipschitz functions. For the role of these classes in optimization we refer also to Georgiev (1997).…”
Section: The Preliminariesmentioning
confidence: 99%
“…In turn, such classes of functions can be equivalently described in geometric terms via the geometric properties of their epigraphs. A notable example is the class of lower-C 2 functions studied by R. T. Rockafellar [Roc81] and the class of proximally smooth sets [CSW95]. We recall that a closed set A of a normed space is R-proximally smooth if the distance function dist(•, A) is continuously differentiable on the open R-neighborhood of the form {x : 0 < dist(x, A) < R}.…”
Section: Introductionmentioning
confidence: 99%
“…then for any fixed (d, r) we have that x → U (x, d, r) is prox-regular and subdifferentially continuous (see [25,Example 2.9]), Clarke regular (see [28]), semismooth (see [21]) and hence submonotone and directionally upper semicontinuous (see [27] and [30]) and g is fully amenable at F (x) when f i ∈ C 2 [28, Example 10.23]. It is thus a very well-behaved function indeed from the standpoint of nonsmooth analysis.…”
mentioning
confidence: 99%
“…Observe that in this case, if f α ∈ C 2 (IR n ) and Λ is finite, then f is locally Lipschitz, prox-regular and subdifferentially continuous (see [25, Example 2.9]). Also f is regular function (see [27] regarding lower C 2 functions) and semismooth (see [21] regarding suprema of semi-smooth functions). Hence by the results of [30] we must have ∂f submonotone and hence directionally continuous.…”
mentioning
confidence: 99%